Teaching LSP for the Baccalaureate Examination: What Syllabuses are we designing? - NAOUA, Mohammed (University of eloued جامعة الوادي, 2017)
Teaching languages for specific purposes (LSP) can be defined as the process of providing homogeneous groups of learners or trainees with specific types of instruction based on extensive analyses of their specific academic or professional communicative needs. The latter refer to the real-world situations, which learners or trainees may respectively encounter during their further studies, or in the work place. Designing syllabuses for such contexts should respond to the following criteria: homogeneity of participants, specificity of content, authenticity of task, and interaction between learners' background knowledge and syllabi content. However, this rule seems to be reversed in Algeria, where heterogeneous LSP classes of learners continue to be provided with the same program of study, which can hardly meet the requirements of one out of the seven specialties studying at the secondary cycle. This paper attempts to conduct an empirical analysis to examine the suitability of the third year syllabus in secondary education to the pupils' communicative needs.
Colloque International Langues, Employabilité et Enseignement Supérieur - Université Oran 2
Keywords: Baccalaureate examination, Communicative Competence , LSP, Needs ,Syllabus Design